(untitled) (Damascus University Journal for legal sciences, 2024)
After the simplified joint stock company has proved its importance in stimulating the economy and developing the business environment, through the success of several countries, such as France, the Kingdom of Morocco and Colombia, in benefiting from its advantages which combines the characteristics of people and money companies, within a legal framework that protects the partners and developing the investment environment, so the existence of this company has become so important. This made this study important in explaining the effectiveness of the role assigned to the simplified joint-stock company in stimulating the economy and developing the business environment, by removing the ambiguity in the concept of the simplified joint-stock company, and clarify the legal provisions governing the company.